Utilizing Infographics to Develop EFL Functional Writing Skills of Prospective Teachers - سارة نجيب (Faculty of Education - Port Said University, 2022)
AbstractThis study examined the effect of infographics on developing EFL functional writing skills of prospective teachers at Faculty of Education. The one group pre-posttest quasi experimental design was utilized to investigate the effect of the suggested infographics-based education on prospective teachers' functional writing. The sample of the study consisted of seventy third year prospective teachers enrolled, in the academic year 2021/2022, in the English Department, Faculty of Education, Port Said University. They were taught to present required written productions, including reports, research projects, formal e-mails, lesson plans, written instructions, summaries, formal letters, and curriculum vitae, in the target language competently. The instrument included pre-posttest of EFL functional writing skills that was prepared and administered by the researcher to investigate the development in the participants' functional writing skills before and after the administration of the infographics-based education. A rubric was prepared to assess participants' responses to the pre-post EFL functional writing test in relation to three main categories: designing of format, composition of content, and appropriateness of language. The results of the study revealed that infographics were effective in developing EFL functional writing skills as they helped prospective teachers write more systematically and logically. The changes in the participants' written production demonstrated competent comprehension of the required format, content, and language. Keywords: functional writing, prospective teachers, infographics, TEFL.